Effects of outer top gas injection on ICRF coupling in ASDEX Upgrade: towards modelling of ITER gas injection. (18th May 2017) - Zhang, W; Bobkov, V; Noterdaeme, J-M; Tierens, W; Bilato, R; Carralero, D; Coster, D; Jacquot, J; Jacquet, P; Lunt, T; Pitts, R A; Rohde, V; et al.
Abstract: The influence of outer top gas injection on the scrape-off layer (SOL) density and ion cyclotron range of frequency (ICRF) coupling has been studied in ASDEX Upgrade (AUG) L-mode plasmas for the first time. The three-dimensional (3D) edge plasma fluid and neutral transport code EMC3-EIRENE is used to simulate the SOL plasma density, and the 3D wave code RAPLICASOL is used to compute the ICRF coupling resistance with the calculated density. Improvements have been made in the EMC3-EIRENE simulations by fitting transport parameters separately for each gas puffing case. It is found that the calculated local density profiles and coupling resistances are in good agreement with the experimental ones. The results indicate that the SOL density increase depends sensitively on the spreading of the injected outer top gas. If more gas enters into the main chamber through the paths near the top of vessel, the SOL density increase will be more toroidally uniform; if more gas chooses the paths closer to the mid-plane, then the SOL density increase will be more local and more significant. Among the various local gas puffing methods, the mid-plane gas valve close to the antenna is still the best option in terms of improving ICRF coupling. Differences between the outer top gas puffing in AUG and the outer top gas puffing in ITER are briefly summarized. Instructive suggestions for ITER and future plans for ITER gas injection simulations are discussed.